Implementation Of The Simple Additive Weighting Method At Universitas Terbuka Mataram For New Employee Recruitment - Husain, Husain; Santoso, Heroe; Wardhana, Helna; Ardiasyah, Muhammad Irwan; Fitriani, Nurul (Universitas Bumigora Mataram-Lombok, 2022)
An agency will thrive if it is supported by qualified employees. So that employees are certainly one of the most important assets in an institution, both private and public institutions, so that agencies are required to recruit prospective contract employees who have competence and talent to support the implementation of work at the Open University of Mataram City. Skilled workers who can bring institutions forward and compete with other agencies so that they can keep up with the times, and the recruitment aspect is starting to get a special view, because the recruitment process is not in accordance with the needs at the Mataram Open University so that it can hinder the rate of development of the agency itself. Therefore, a decision support system is needed for the contract employee recruitment process at the Universitas Terbuka Mataram. Therefore, a decision support system is needed for the contract employee recruitment process at universitas Terbuka Mataram campus. This decision support system uses the Simple Additive Weighting SAW method. In this case, prospective employees are compared with one another so as to provide an output value of priority intensity which results in a system that provides an assessment of each employee. This decision support system helps evaluate each employee, make changes to the criteria, and changes the weight values. This is useful to facilitate decision making related to employee selection issues, so that the most appropriate employees will be received in the company. The purpose of this study was to select the best candidate for employees at the Universitas Terbuka Mataram. The results of this study indicate that the SAW method is appropriate for selecting the best prospective employees because it can obtain qualified employees in accordance with the expectations of the company and the leadership.